Effects of α-amylase and coated α-amylase supplementation on growth performance, nutrient digestion, and rumen fermentation in Holstein bulls - Zhang, Xiaoming; Xue, Feng; Xu, Kailin; Liu, Qiang; Guo, Gang; Huo, Wenjie; Zhang, Yawei; Wang, Cong (Frontiers in Veterinary Science, 2024)
This current work evaluated the impacts of α-amylase (AM) and coated α-amylase (CAM) on bull performance, nutrient digestibility and ruminal fermentation. This study randomized sixty Holstein bulls of 365 ± 11.5 days age and 457.5 ± 9.35 kg body weight into three groups: without AM addition, adding AM 0.6 g/kg dry matter (DM) and adding CAM 0.6 g AM/kg DM, separately. This whole experimental period was 80 days, including a 20-day adaptation period and a 60-day data and sample acquisition period. In comparison with the unsupplemented control, dry matter intake (DMI) was unaltered, but average daily gain (ADG) and feed efficiency (FE) were greater for AM or CAM addition. Bulls receiving AM or CAM supply had greater total-tract nutrient digestibility, ruminal total volatile fatty acids (VFA) content, propionate molar proportion, cellulolytic enzyme and AM activities and the number of microorganisms. In addition, the activities of AM and trypsin in the jejunum and ileum and glucose, albumin and total protein concentrations in serum were greater for AM or CAM addition compared with control. When comparing the supplementation mode of AM, bulls receiving CAM addition had greater ADG and FE . The crude protein and starch digestibility and intestinal AM and trypsin activity were greater, and acid detergent fiber (ADF) digestibility was lower for CAM addition than for AM addition. The lower propionate molar proportion, cellobiase and carboxymethyl-cellulase activities, together with Ruminococcus albus, Ruminococcus flavefaciens and Fibrobacter succinogenes populations were observed for CAM addition compared with AM addition. However, there were greater glucose, albumin and total protein concentrations in serum after adding CAM. According to the data, the supply of AM improved ADG, nutrient digestion and rumen fermentation. Notably, the optimum supplementation mode was in the form of CAM in bulls.